Clinical, biochemical, and pathophysiological analysis of SLC34A1 mutations. Issue 12 (19th June 2018) - Fearn, Amy; Allison, Benjamin; Rice, Sarah J.; Edwards, Noel; Halbritter, Jan; Bourgeois, Soline; Pastor‐Arroyo, Eva M.; Hildebrandt, Friedhelm; Tasic, Velibor; Wagner, Carsten A.; Hernando, Nati; Sayer, John A.; et al.
Abstract: Mutations in SLC34A1, encoding the proximal tubular sodium–phosphate transporter NaPi‐IIa, may cause a range of clinical phenotypes including infantile hypercalcemia, a proximal renal Fanconi syndrome, which are typically autosomal recessive, and hypophosphatemic nephrolithiasis, which may be an autosomal dominant trait. Here, we report two patients with mixed clinical phenotypes, both with metabolic acidosis, hyperphosphaturia, and renal stones. Patient A had a single heterozygous pathogenic missense mutation (p.I456N) in SLC34A1, consistent with the autosomal dominant pattern of renal stone disease in this family. Patient B, with an autosomal recessive pattern of disease, was compound heterozygous for SLC34A1 variants; a missense variant (p.R512C) together with a relatively common in‐frame deletion p.V91A97del7 (91del7). Xenopus oocyte and renal (HKC‐8) cell line transfection studies of the variants revealed limited cell surface localization, consistent with trafficking defects. Co‐expression of wild‐type and I456N and 91del7 appeared to cause intracellular retention in HKC‐8, whereas the R512C mutant had a less dominant effect. Expression in Xenopus oocytes failed to demonstrate a significant dominant negative effect for I456N and R512C; however, a negative impact of 91del7 on [ 32 P]phosphate transport was found. In conclusion, we have investigated pathogenic alleles of SLC34A1 which contribute to both autosomal dominant and autosomal recessive renal stone disease. Abstract : Mutations in SLC34A1, encoding the proximal tubular sodium–phosphate transporter NaPi‐IIa, may cause a range of clinical phenotypes including infantile hypercalcemia, a proximal renal tubulopathy, and hypophosphatemic nephrolithiasis. Here, we report two patients with mixed clinical phenotypes, both with metabolic acidosis, hyperphosphaturia, and renal stones. Here, we investigate using oocyte and cell transfection studies the underlying pathogenic alleles of SLC34A1 .